Aplicação da Metodologia de Custeio ABC para análise dos custos logísticos no processo de aditivação de combustíveis em um terminal de distribuição - Silva Neto, Elias Duarte da (2020)
In the context of intense globalization and competition, the concept of process management, in particular those arising from logistics costs, becomes more recurrent in discussions because they can guarantee competitive advantages.for companies. thus, was elaborated this research work whose objective is to demonstrate, through analyze of logistics costs the comportament of results of a fuel distribution terminal located at ceará, after implantation of improvements in the fuel additive process. the case study was developed to detail themes necessary to the company’s knowledge and to the process review, identification and measurement of costs resulting from logistics activities in the current and proposed additive process, description of proposed process improvements and application of the activity based costing to identify costs related to each of the activities. with the study, it was possible to realize the impact of the logistics costs in fuel additives the results showed that the proposed changes to the fuel additive process are consistent with the need to ensure competitive advantages in the logistics industry.